In vitro and in vivo silencing of plasmodial dhs and eIf-5a genes in a putative, non-canonical RNAi-related pathway - Schwentke, Andreas; Müller, Ann-Kristin; Hammerschmidt-Kamper, Christiane (BMC microbiology, 2012)
Background Deoxyhypusine synthase (DHS) catalyzes the first step in hypusine biosynthesis of eukaryotic initiation factor 5A (eIF-5A) in Plasmodium falciparum. Target evaluation of parasitic DHS has recently been performed with CNI-1493, a novel selective pro-inflammatory cytokine inhibitor used in clinical phase II for the treatment of Crohn's disease. CNI-1493 prevented infected mice from experimental cerebral malaria by decreasing the levels in hypusinated eIF-5A and serum TNF, implicating a link between cytokine signaling and the hypusine pathway., Therefore we addressed the question whether either DHS itself or eIF-5A is required for the outcome of severe malaria. In a first set of experiments we performed an in vitro knockdown of the plasmodial eIF-5A and DHS proteins by RNA interference (RNAi) in 293 T cells. Secondly, transfection of siRNA constructs into murine Plasmodium schizonts was performed which, in turn, were used for infection. Results 293 T cells treated with plasmodial DHS- and eIF-5A specific siRNAs or control siRNAs were analyzed by RT-PCR to determine endogenous dhs -and eIF-5A mRNA levels. The expressed DHS-shRNA and EIF-5A-shRNA clearly downregulated the corresponding transcript in these cells. Interestingly, mice infected with transgenic schizonts expressing either the eIF-5A or dhs shRNA showed an elevated parasitemia within the first two days post infection which then decreased intermittently. These results were obtained without drug selection. Blood samples, which were taken from the infected mice at day 5 post infection with either the expressed EIF-5A-shRNA or the DHS-shRNA were analyzed by RT-PCR and Western blot techniques, demonstrating the absence of either the hypusinated form of eIF-5A or DHS. Conclusions Infection of NMRI mice with schizonts from the lethal P. berghei ANKA wildtype strain transgenic for plasmodial eIF-5A-specific shRNA or DHS-specific shRNA resulted in low parasitemia 2-9 days post infection before animals succumbed to hyperparasitemia similar to infections with the related but non-lethal phenotype P. berghei strain NK65. RT-PCR and Western blot experiments performed with blood from the transfected erythrocytic stages showed that both genes are important for the proliferation of the parasite. Moreover, these experiments clearly demonstrate that the hypusine pathway in Plasmodium is linked to human iNos induction.
Published: 13 June 2012
Gesehen am 12.06.2018